The Importance Of Youth Lexicon Dictionaries In Linguistics - Saidova Durdona Akrom qizi (Global Scientific Publishing, 2025)
This article discusses the concept of youth lexicon, the dictionaries related to youth language, and their specific characteristics
Keywords: youth lexicon; colloquial language; youth language